Ned - Daddo, Andrew (Melbourne, Victoria : Penguin Australia, 2014)
STUFF HAPPENS is a contemporary reflected reality fiction series for young boys. Each book tells the story of an incident of emotional importance to one of the boys in a fictional primary school class. The stories, written by some of Australia's finest male writers, make an important contribution to the emotional literacy of Australian boys.
For children.
Keywords: Boys -- Juvenile fiction; Emotions -- Juvenile fiction; Schools -- Juvenile fiction; Teachers -- Juvenile fiction; Families -- Juvenile fiction; School -- Juvenile fiction; Australian; Children's stories